PENERAPAN PIDANA TERHADAP PENyALAH GUNA NARKOTIKA UNTUK DIRINyA SENDIRI - Dahlan Dahlan (UNISSULA, 2017)
Article 2 of Law Number 35 Year 2009 on Narcotics mentioned Narcotics Act based on Pancasila and the Constitution of the State of the Republic of Indonesia Year 1945. Subsequently Article 3 letter a mentioned Narcotics Act held based on keadilah. But in his enforcement does not describe the sense of justice. This research is normative juridical, that is method whichdescribes or exposes a fact systematically then its analysis is conducted by juridical by linking between data and facts obtained by analyzing court decision related to criminal sanction to perpetrator of narcotic crime and related with regulation of law applicable. In order to achieve a common perception in the application of narcotic drug abuse for himself by law enforcement officials, it is necessary to reconstruct Law Number 35 Year 2009 on Article 132 Paragraph (1) to be: Experiment or conspiracy to commit narcotic crime and narcotics precursor as referred to in Article 111, Article 115, Article 119, Article 120, Article 121, Article 122, Article 123, Article 124, Article 125, Articles 126, 127, And Article 129, the perpetrator shall be subject to the same imprisonment in accordance with the provisions referred to in those Articles